Deacylcynaropicrin from Cyclolepis genistoides as cytoprotective agent against oxidative stress - Alza, Natalia Paola (2023)
Oxidative stress (OS) is considered a common pathological mechanism in many diseases. Specifically in neurodegenerative disorders, OS directly or indirectly triggers neuronal death as a consequence of mitochondrial dysfunction, proteostasis alterations, inflammation, and dysregulation of antioxidant defenses. The aim of our work was to evaluate the potential neuroprotective effect of the aqueous extract of Cyclolepis genistoides D. Don (Asteraceae) and bioactive constituents against cellular OS. This species has been used in folk medicine in Northern and central Argentina for bone pain (analgesic properties) and kidney diseases, and as a diuretic. In our lab, we selected C. genistoides from a screening of Argentinian medicinal plants based on its ability to reduce OS induced by iron in IMR-32 neuroblastoma cells by means of a reduction of reactive oxygen species production and lipid peroxidation (at 20 μg/ml). LC-MS/MS analysis of the aqueous extract showed the presence of phenolic compounds (such as caffeoylquinic acids, luteolin and its glucuronide) and two sesquiterpene lactones, deacylcynaropicrin (DACP) and its 11,13-dihydro derivative. A bioguided fractionation of C. genistoides extract afforded the isolation of DACP. To elucidate the biological effect of DACP, the cellular response against OS was studied in the presence of the compound using IMR-32 cells exposed to ferric ammonium citrate (FAC) as OS inducer. DACP at 10 and 20 μM was able to inhibit reactive oxygen species production in FAC-exposed cells. The potential mechanism by which DACP reduces cellular OS was investigated through its action on two redox-sensitive transcription factors, NFR2 and NF B. During iron-induced OS, DACP exposure rendered the nuclear translocation of NRF2, associated with the expression of antioxidant genes. One of them is the glutamate-cysteine ligase catalytic subunit, which was upregulated in the presence of DACP. Interestingly, the same effect was observed in cells exposed to C. genistoides extract. Moreover, NF B (involved in the inflammatory response) nuclear translocation induced by FAC was blocked by DACP. Our results suggest that DACP is responsible for the biological activity of C. genistoides aqueous extract and could be a neuroprotective agent during iron-induced OS scenarios.